2011
DOI: 10.1002/arch.20420
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological response patterns of 16 olfactory neurons from the trichoid sensilla to odorant from fecal volatiles in the locust, locusta migratoria manilensis

Abstract: Locusts are the most serious pests of crops in greater part of the world. They locate their host plants primarily through olfactory cues, using antennal chemosensilla, which house olfactory receptor neurons (ORNs). Despite the great economical interest of these species, their olfactory neurons have been poorly investigated at the functional level. In this study, we have used single sensillum recordings (SSRs) to obtain response patterns of ORNs from the antennal trichoid sensilla to various chemicals in the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…Additional confirmation needs to be performed to test the activities of these same odorants that are active in LmigOR3 transgenic Drosophila aT1 system on locust antennal trichoid sensilla, because additional families of proteins, such as odorant-binding proteins (OBPs) (Pelosi et al, 2006), and sensory neuron membrane proteins (SNMPs) (Jin et al, 2008), are believed to be involved in odorant recognition. For instance, benzaldehyde elicited inhibitory responses for all trichoid sensilla in locusts (Cui et al, 2011), but we observed weak excitatory responses from LmigOR3 expressed in transgenic flies. It is possible LmigOR3 is expressed in trichoid sensilla that have escaped previous characterization, or that the response in vivo relies on additional factors, such as OBPs (Grosse-Wilde et al, 2007; Laughin et al, 2008; Leal, 2013).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Additional confirmation needs to be performed to test the activities of these same odorants that are active in LmigOR3 transgenic Drosophila aT1 system on locust antennal trichoid sensilla, because additional families of proteins, such as odorant-binding proteins (OBPs) (Pelosi et al, 2006), and sensory neuron membrane proteins (SNMPs) (Jin et al, 2008), are believed to be involved in odorant recognition. For instance, benzaldehyde elicited inhibitory responses for all trichoid sensilla in locusts (Cui et al, 2011), but we observed weak excitatory responses from LmigOR3 expressed in transgenic flies. It is possible LmigOR3 is expressed in trichoid sensilla that have escaped previous characterization, or that the response in vivo relies on additional factors, such as OBPs (Grosse-Wilde et al, 2007; Laughin et al, 2008; Leal, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…2-heptanone is the component of maize leaf volatiles (Buttery and Ling, 1984) as well as that of locust body volatiles (Li and Zhang, 2011). 2, 5-dimethylpyrazine is the component of locust body volatiles (Cui et al, 2011; Yu et al, 2007). Previously, 16 types of neurons in 7 subtypes of trichoid sensilla were identified by electrophysiology (at2-1, at2-2, at2-3, at2-4, at2-5, at3-1, at3-2) in locust antennae in response to 9 odors (octanal, hexanal, 2, 5-dimethylpyrazine, 2, 6, 6-trimethyl-2-cyclohexene-1, 4-dione, trans-2-hexenal, cyclohexanol, 2-heptanone, guaiacol, benzaldehyde) present in fecal volatiles in the locust (Cui et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORNs expressing the same ORs were housed in electrophysiologically identical sensilla subtypes and converged to the same glomerulus in the antennal lobe. Extracellular single-unit recordings from individual olfactory sensilla have revealed that different odorants elicit responses from different subsets of ORNs, and that ORNs exhibit a remarkable diversity of response properties [3,4,21]. ORNs housed in different sensilla types expressed distinct ORs, allowing the sensilla to be characterized by their molecular and cellular properties [2,4,19,21-23].…”
Section: Introductionmentioning
confidence: 99%
“…In locust, behaviours underlying aggregation and food seeking heavily depend on volatile compounds emitted from conspecifics or plants, respectively 2. These chemical signals are mainly detected by olfactory sensory neurons (OSNs) on the antennae 3, 4, which project their chemoreceptive dendrites into morphologically different types of cuticular hair structures (olfactory sensilla). Based on their morphology and cell numbers different types of antennal olfactory sensilla are discriminated: sensilla basiconica housing 20-50 OSNs and sensilla trichodea containing 1-3 OSNs 5, 6.…”
Section: Introductionmentioning
confidence: 99%